Characterizing disease manifestations and treatment outcomes among patients with orofacial granulomatosis in ChinaCapsule Summary - Minghui Wei, MM; Cheng Xie, MD, PhD; Yubo Liu, MM; Yuhong Wang, MM; Yuanyuan Wang, MM; Xinwen Wang, MD, PhD; Yuan Liu, MD, PhD (Elsevier, 2020)
Background: Racial variation exists in the incidence of orofacial granulomatosis (OFG). The epidemiology and clinical characteristics of OFG in Asian countries are poorly described. Objective: To describe the epidemiologic and clinical features of OFG in China from data collected on chronic odontogenic infection and studied in actual practice regarding the long-term outcome of OFG patients receiving different treatments. Methods: Data on demographics, medical history, chronic odontogenic infection, and the extent of disease were collected, and long-term outcomes after the end of treatments were evaluated. Results: Of the 165 OFG patients, 118 (71.5%; 95% CI 64.6%-78.5%) had a chronic odontogenic infection. There was a variety of difference between OFG with and without chronic odontogenic infection. Approximately 98.3% (95% confidence interval 94.8%-100%) of OFG patients with chronic odontogenic infection who received dental treatment showed a marked response, of whom 31 patients (53.4%; 95% confidence interval 40.2%-66.7%) had complete remission. Limitations: Endoscopic investigations were not performed for most of the patients, and more detailed data were not collected, which might have demonstrated additional systemic problems. Conclusions: OFG with chronic odontogenic infection is the major clinical pattern of OFG in China, which may be a subtype of OFG. Dental treatment should necessarily be the preferred first-line therapy for such patients.